2021
DOI: 10.3390/nu13082889
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between 25 Hydroxyvitamin D, Overweight/Obesity Status, Pro-Inflammatory and Oxidative Stress Markers in Patients with Type 2 Diabetes: A Simplified Empirical Path Model

Abstract: Vitamin D deficiency is highly prevalent in patients with overweight/obesity and type 2 diabetes (T2DM). Herein, we investigated the relationship between vitamin D status and overweight/obesity status, insulin resistance (IR), systemic inflammation as well as oxidative stress (OS). Anthropometric and laboratory assessments of 25-hydroxyvitamin D (25(OH)D) and glycemic, pro-inflammatory and OS biomarkers were performed in a sample of 47 patients with T2DM who were divided into categories based on overweight and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 62 publications
0
7
1
Order By: Relevance
“…These results were in line with those of our study; in males, in the logistic regression analysis, WC and BMI were associated with vitamin D deficiency. Nevertheless, these results disagreed with those of Cătoi et al [61], who explored the complex relationship between the levels of 25(OH)D and overweight/obesity, insulin resistance, systemic inflammation, and oxidative stress, revealing that overweight and an increasing degree of obesity were not significantly associated with a decrease in the levels of 25(OH)D.…”
Section: Discussioncontrasting
confidence: 96%
“…These results were in line with those of our study; in males, in the logistic regression analysis, WC and BMI were associated with vitamin D deficiency. Nevertheless, these results disagreed with those of Cătoi et al [61], who explored the complex relationship between the levels of 25(OH)D and overweight/obesity, insulin resistance, systemic inflammation, and oxidative stress, revealing that overweight and an increasing degree of obesity were not significantly associated with a decrease in the levels of 25(OH)D.…”
Section: Discussioncontrasting
confidence: 96%
“…An inverse relationship between circulating vitamin D levels and different biomarkers related to oxidative stress and inflammation has been found in subjects with cardiometabolic risk or patients with CV disease. In particular, obese subjects (children and adolescents or adults) or T2D patients with hypovitaminosis D presented elevated levels of oxidative stress and inflammatory biomarkers, and an inverse correlation is also found between 25(OH)D and levels of different oxidative stress and inflammatory biomarkers [ 146 , 147 , 148 , 149 , 150 , 151 ]. In coronary artery disease (CAD) patients, an inverse relationship between vitamin D and homocystine (Hcy) was observed.…”
Section: Observational Studiesmentioning
confidence: 99%
“…Numerous studies have linked vitamin D deficiency to metabolic disorders, such as increased levels of inflammation, oxidative stress, reactive oxygen species (ROS) production, insulin resistance, endothelial dysfunction, and disruption of blood sugar and lipids, which contribute to an increased risk of cardiovascular disease ( 29 31 ). Recently, Cãtoi et al ( 32 ) conducted a cross-sectional study to investigate the association between 25(OH)D and markers of oxidative stress in 47 patients with type 2 diabetes. They found that compared to those with serum 25(OH)D greater than 20 ng/mL, interleukin 6, total oxidant status and oxidative stress index were significantly higher in the 25(OH)D less than 10 ng/mL and 25(OH)D between 10 and 20 ng/ml group.…”
Section: Discussionmentioning
confidence: 99%